RETRACTED: Scientific tourism as a promising direction for the development of the tourism sector of the Rostov region, Russia - Mukhametgalieva Victoria; Bakhtin Victor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001